Investigating the Use of Language Learning Strategies and English Proficiency of University Students - Virginia Gabrella Sengkey (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
This study used descriptive and correlational research designs to identify the levels of students’ language learning strategies use (LLS) and their English proficiency and whether there is a significant correlation between the two variables. The sample of this study consisted of 56 students majoring in English enrolled in Listening and Speaking classes at a private university in North Sulawesi. The instruments used in this study were Oxford's SILL (1990) to measure the students' LLS and students' final test scores to assess their English proficiency. The results showed that the students usually use LLS with metacognitive strategies as the most commonly used strategy. Moreover, the results also showed that the students had good English proficiency. However, the students’ LLS use did not significantly correlate with their English proficiency. Hence, further research can be conducted to provide insights into why students have good English proficiency.